Preparation method of defect-rich hollow open bismuth phosphate microsphere negative electrode material
Through the etching and calcining of Bi-metal organic frame material, a hollow bismuth phosphate microsphere negative electrode material with a multi-layer pore structure is formed, which solves the problems of electron transfer and dead volume in electrochemical energy storage devices, and significantly improves electrochemical storage Energy efficiency and capacity retention.
Patent Information
- Application Number
- CN202411409622.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to achieve rapid electron transfer in electrochemical energy storage devices and reduce the "dead volume" of the material, resulting in low electrochemical energy storage efficiency.
Bi-metal organic frame material (MOFs) is used as the precursor, and a hollow bismuth phosphate microsphere negative electrode material with a multi-layer pore structure is formed through organic acid etching strategy. The calcination atmosphere is changed to optimize the material components and crystal phases to build a high-performance electrode Material.
The mass transfer kinetics and electrochemical active sites of the material are significantly improved, and the electrochemical energy storage performance with high capacity ratio and long life is achieved, especially under high current density conditions.
Smart Images

Figure CN119284850A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional nanocomposite materials, and in particular relates to a method for preparing a defect-rich hollow open bismuth phosphate microsphere negative electrode material. Background Art
[0002] In order to overcome the problem of uneven distribution of clean energy in time and space, how to transport and store clean energy has become a major difficulty. Therefore, the design and development of high-performance electrochemical energy storage devices has become an important area of scientific research focus.
[0003] Aqueous alkaline rechargeable batteries are electrochemical devices that achieve energy storage based on ion adsorption or redox reactions on the surface of electrode materials. They have the advantages of high safety, long cycle life, and environmental friendliness, and have attracted widespread attention from the scientific community. The performance of electrode materials is a key factor in determining electrochemical energy storage devices. Therefore, designing and optimizing the composition and structure of electrode materials, constructing multi-level channels inside the materials, reducing the center of gravity utilization and dead volume, and breaking through mass transfer limitations are the key directions for building "double-high" electrochemical energy storage devices.
[0004] As a nitrogen-based nonmetal, phosphorus is an excellent coordination atom in coordination chemistry and can react with a variety of metal / nonmetal elements to form a variety of phosphides or phosphates. In addition, the high self-support and stoichiometry of the phosphorus skeleton make its derivatives have a variety of crystal structures. Similar to carbon-based materials, the micro-nanostructure of transition metal phosphates is highly adjustable, and its large pore channels and open cavity skeleton give it excellent ion / charge conductivity, and it is widely used in pseudocapacitive electrodes as a good "substitute" for carbon-based electrode materials. Metal-organic framework materials (MOFs) are porous crystalline materials formed by self-assembly of metal ions or clusters and organic ligands through coordination bonds. In recent years, multi-level carbon-based nanoelectrode materials constructed based on MOFs as sacrificial templates have attracted widespread attention due to their advantages such as high specific surface area, rich pore structure, and easy functionalization by other heteroatoms. Despite this, how to quickly transfer electrons to the interior of the material and thus reduce the "dead volume" of the material remains a major obstacle.
[0005] The MOFs etching strategy is an in situ ion exchange reaction based on the reversibility of coordination bonds, which replaces metal ions or ligand anions in MOFs with ions with stronger coordination ability, and finally achieves MOFs modification or phase transformation. Based on this, constructing hollow MOFs-derived electrode materials with multi-level pore structures is a challenge for modern nanotechnology and an opportunity to improve electrochemical energy storage devices. Summary of the invention
[0006] The purpose of the present invention is to solve the above-mentioned problems existing in the prior art. A preparation method of defect-rich hollow open bismuth phosphate microsphere negative electrode material is proposed. Bi-metal organic framework material (MOFs) is used as a precursor, and then an organic acid etching strategy is used to replace the ligand anions in MOFs with ions with stronger coordination ability to form a multi-level pore structure of micropores / mesoporous in the metal organic framework. The transformation of material components or crystal phases is achieved by changing the calcination atmosphere, and high-performance electrode materials are continuously optimized and screened to construct a "double high" bismuth-based aqueous alkaline rechargeable battery system.
[0007] The technical solution of the present invention is:
[0008] The present invention provides a method for preparing a defect-rich hollow open bismuth phosphate microsphere negative electrode material, comprising the following steps:
[0009] (1) dissolving bismuth nitrate pentahydrate and trimesic acid in a molar ratio of 1:(1-2) in an organic solvent, and performing a solvothermal reaction at 140-160° C. to obtain a spherical Bi-BTC MOFs precursor;
[0010] Wherein, the organic solvent comprises ethanol and ethylene glycol, and the volume ratio of the ethanol to the ethylene glycol is 1:(1-3);
[0011] The molar ratio of bismuth nitrate pentahydrate to trimesic acid is 1:(1-3), for example, 1:1, 1:1.3, 1:1.4, 1:1.43, 1:1.45, 1:1.47, 1:1.5, 1:1.8, 1:2, 1:2.3, 1:2.5, 1:2.8 or 1:3, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0012] Preferably, the molar ratio of bismuth nitrate pentahydrate to trimesic acid is 1:1.42.
[0013] The reaction temperature is 140-160°C, for example, it can be 140°C, 143°C, 145°C, 147°C, 150°C, 152°C, 155°C, 157°C or 160°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0014] The volume ratio of ethanol to ethylene glycol is 1:(1-3), for example, it can be 1:1, 1:1.3, 1:1.4, 1:1.5, 1:1.7, 1:2, 1:2.3: 1:2.5, 1:2.7 or 1:3, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0015] (2) dispersing the precursor into deionized water to form a homogeneous solution, adding a phytic acid solution with a concentration of 0.05 to 0.2 mol / L, and reacting in an oil bath at 80 to 100° C. for 0.5 to 5 h to obtain a BPHM nanomaterial;
[0016] The above phytic acid concentration is 0.05-0.2 mol / L, for example, it can be 0.05 mol / L, 0.1 mol / L, 0.15 mol / L or 0.2 mol / L, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0017] The oil bath temperature is 80-100°C, for example, it can be 80°C, 83°C, 85°C, 87°C, 90°C, 93°C, 95°C, 97°C or 100°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0018] The oil bath reaction time is 0.5 to 5 h, for example, it can be 0.5 h, 0.8 h, 1 h, 1.3 h, 1.5 h, 1.7 h, 2.0 h, 2.5 h, 2.8 h, 3.0 h, 3.2 h, 3.5 h, 3.8 h, 4 h, 4.2 h, 4.5 h, 4.8 h or 5 h, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0019] (3) The prepared nanomaterial is calcined at 400-500° C. for 1-3 h to obtain defect-rich hollow open bismuth phosphate microspheres, which can be used as negative electrode materials.
[0020] The temperature of the high temperature calcination reaction is 400-500°C, for example, 400°C, 410°C, 420°C, 450°C, 470°C, 480°C or 500°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0021] The reaction time is 1 to 3 hours, for example, 1 hour, 1.3 hours, 1.5 hours, 1.7 hours, 2.0 hours, 2.5 hours, 2.8 hours or 3 hours, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0022] The present invention uses ethanol and ethylene glycol as organic solvents, and regulates the reaction temperature and time, thereby effectively maintaining the unique metal coordination framework structure of the spherical precursor, and then performs an oil bath etching reaction to replace the ligand anions in the spherical precursor with ions with stronger coordination ability, and finally performs a high-temperature calcination reaction, which not only maintains the spherical structure but also increases the structural stability of the material, and finally prepares a hollow nanoelectrode material with a multi-level pore structure, exposing more electrochemically active sites.
[0023] Furthermore, in the step (1), bismuth nitrate pentahydrate and trimesic acid are first dissolved in a mixed solution of ethanol and ethylene glycol in a volume ratio of 1:(1-3) in a molar ratio of 1:(1-2), ultrasonically dispersed for 20 minutes, and then subjected to a solvothermal reaction at 140-160° C. for 24 hours. The mixture is cooled to room temperature, the precipitate is collected, centrifuged and washed, and then dried at 60° C. for 12 hours to obtain a spherical Bi-BTC MOFs precursor.
[0024] The purpose of ultrasonic dispersion in step (1) is to synthesize a Bi-BTC precursor with relatively uniform morphology and size.
[0025] Furthermore, in the step (1), the amount of the organic solvent added satisfies: bismuth nitrate pentahydrate and trimesic acid are completely dissolved in the organic solvent.
[0026] Furthermore, the oil bath reaction time in step (2) is 1 to 4 hours. Preferably, the oil bath reaction time is 3 hours.
[0027] Furthermore, in the step (2), the Bi-BTC MOFs precursor is dispersed in deionized water, and the mass volume ratio of the precursor to deionized water is 0.1 g: 10 mL; after dispersion to form a homogeneous solution, 0.05-0.2 mol / L of phytic acid solution is added to control the mass ratio of Bi-BTC and phytic acid in the final reaction system to be 1:1.65-66; finally, the reaction is carried out in an oil bath at 90°C for 0.5-5h, centrifuged, and dried to obtain BPHM-X nanomaterials; wherein X represents the reaction time.
[0028] Deionized water and phytic acid solution are added to the precursor of the above step (2) in sequence, the mass volume ratio of the precursor to deionized water is 1:100 (g / mL), and the mass ratio of Bi-BTC and phytic acid in the reaction system is controlled to be 1:1.65-66. For example, when the mass of the precursor is 0.1g, the amount of deionized water added is 10mL, and the amount of phytic acid solution (concentration is 0.05-0.2mol / L) added is controlled to be 5-50mL. The specific amount added can be 5mL, 10mL, 15mL, 20mL, 25mL, 30mL, 35mL, 40mL, 45mL or 50mL, but is not limited to the listed values, and other values not listed in this range are also applicable.
[0029] Furthermore, in the step (3), the prepared BPHM nanomaterial is subjected to a high-temperature calcination reaction, the high-temperature calcination temperature is 400-500°C, the heating rate is 2°C / min; the calcination atmosphere is Air, and the reaction time is 1-3h, to obtain defect-rich hollow open bismuth phosphate microspheres.
[0030] The present invention also provides defect-rich hollow open bismuth phosphate microspheres prepared by any of the preparation methods described above.
[0031] The present invention further provides an application of defect-rich hollow open bismuth phosphate microspheres prepared by any of the preparation methods described above. The defect-rich hollow open bismuth phosphate microspheres are used as negative electrode materials in a bismuth-based aqueous alkaline rechargeable battery system.
[0032] Beneficial effects of the present invention:
[0033] The present invention provides a method for preparing defect-rich hollow open bismuth phosphate microsphere negative electrode material, and adopts MOFs etching strategy to construct a hollow nano-electrode material modified with a multi-level pore structure, which can greatly promote large-scale ion diffusion and volume buffering effect, and greatly improve the mass transfer kinetics of the material.
[0034] The defect-rich hollow open bismuth phosphate microsphere negative electrode material prepared by the present invention is used as a negative electrode material in alkaline aqueous batteries. 4 The electrode material has a higher capacity than the commonly reported electrode materials under the same test conditions. The experimental results show that the material is tested under a three-electrode system, 1Ag -1 The current density can reach 844F g -1 When the current density increases 10 times, the specific capacity can still maintain 94% of the initial capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope image of the Bi-BTC MOFs precursor obtained in Example 1;
[0036] Figure 2 is a scanning electron microscope image of BPHM-3 obtained in Example 1;
[0037] Figure 3 is a scanning electron microscope image of BPOHM-3 obtained in Example 1;
[0038] Figure 4 is a transmission electron microscopy image of BPOHM-3 obtained in Example 1;
[0039] Figure 5 This is the mapping diagram of BPOHM-3 obtained in Example 1;
[0040] Figure 6 is the X-ray diffraction pattern of BPOHM-3 obtained in Example 1;
[0041] Figure 7 The constant current charge and discharge curves of BPOHM-3 obtained in Example 1 at different current densities;
[0042] Figure 8 The constant current charge and discharge curves of BPOHM-2 obtained in Example 1 at different current densities;
[0043] Fig. 9 The constant current charge and discharge curves of BPOHM-1 obtained in Example 1 at different current densities;
[0044] Fig.10 The constant current charge-discharge curves of BPOHM-3Ar obtained in Comparative Example 1 at different current densities;
[0045] Fig.11 This is a constant current charge and discharge curve diagram of BPNP-3 obtained in Comparative Example 2 at different current densities. DETAILED DESCRIPTION
[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] In order to further understand the present invention, the present invention will be further described in conjunction with the accompanying drawings and embodiments.
[0048] The experimental methods involved in the following examples are all conventional methods unless otherwise specified. The instruments and reaction materials used are all commercially available unless otherwise specified.
[0049] Example 1
[0050] The present invention provides a method for preparing a defect-rich hollow open bismuth phosphate microsphere negative electrode material, comprising the following steps:
[0051] (1) Preparation of Bi-BTC precursor:
[0052] First, bismuth nitrate pentahydrate and trimesic acid in a molar ratio of 1:1.42 were dissolved in a mixed solution of ethanol and ethylene glycol in a volume ratio of 2:3, ultrasonically dispersed for 20 minutes, transferred to a high-pressure reactor, and subjected to solvothermal reaction at 150°C for 24 hours. After the high-pressure reactor was naturally cooled to room temperature, the precipitate was collected, washed three times by centrifugation with anhydrous ethanol, and then dried in an oven at 60°C for 12 hours to obtain a spherical Bi-BTC MOFs precursor.
[0053] The morphology of Bi-BTC MOFs precursor can be found in Figure 1 Scanning electron microscope image of .
[0054] (2)BiPO 4 Preparation of hollow microsphere (BPHM-X, X=3) nanomaterials:
[0055] Weigh 0.1 g of the Bi-BTC MOFs precursor prepared in step (1), disperse it in 10 mL of deionized water, stir to form a homogeneous solution, and then transfer it to a round-bottom flask and add 15 mL of 0.1 mol L -1 The phytic acid solution was reacted in an oil bath at 90°C for 3 h, and then centrifuged and dried to obtain BPHM-3 nanomaterials.
[0056] The scanning electron microscopy of the sample Figure 2 As shown, the material maintains the spherical morphology of the precursor, but its surface changes from smooth to very rough.
[0057] (3)BiPO 4 Preparation of open hollow microsphere (BPOHM) nanomaterials:
[0058] The BPHM-3 sample obtained in step (2) was placed in a porcelain boat and covered the bottom of the porcelain boat. The porcelain boat was then transferred to a tube furnace and calcined at 450°C and air for 2 h at a heating rate of 2°C min -1 After the tube furnace is naturally cooled to room temperature, the samples are collected to obtain the defect-rich hollow open bismuth phosphate microsphere negative electrode material BPOHM-3.
[0059] For the synthesized materials, the SEM images were Figure 3 As shown in the transmission electron microscopy image Figure 4 The material continues to maintain the spherical morphology of the precursor, the surface of BPOHM-3 becomes rougher and has large holes, and the interior of the material shows a cavity.
[0060] The BPOHM-3 nanomaterials obtained after the reaction were further subjected to mapping tests. Figure 5 As shown in the figure, the material contains Bi, O, and P elements, proving that the hollow porous BiPO 4 Successful synthesis of materials.
[0061] The X-ray diffraction (XRD) results of the prepared materials are shown in Figure 6 As shown, it is proved that the phase of BPOHM-3 material is BiPO 4 (PDF#15-0767).
[0062] The constant current charge and discharge curves (GCD) of this material at different current densities are shown in Figure 2. Figure 7 As shown in the figure, it is calculated that the material is 1Ag -1The specific capacity at a current density of 844 F g -1 .
[0063] The defect-rich hollow open bismuth phosphate microsphere negative electrode material BPOHM-3 prepared above was applied in aqueous alkaline rechargeable batteries. The experiment found that the BPOHM-3 nanomaterial has excellent electrochemical performance as an electrode. Tested under a three-electrode system, 1Ag -1 At a current density of 844 F g -1 When the current density increases 10 times, the specific capacity can still maintain 94% of the initial capacity.
[0064] Example 2
[0065] The difference between this embodiment and embodiment 1 is that the etching time of the Bi-BTC MOFs precursor in step (2) is 1 hour to obtain BPHM-1 nanomaterial. The other conditions are the same.
[0066] The constant current charge-discharge (GCD) curves of the finally prepared defect-rich hollow open bismuth phosphate microsphere negative electrode material BPOHM-1 at different current densities are shown in the figure. Figure 8 As shown, it is calculated that the material is 1Ag -1 The specific capacity at a current density of 1.377 W / m can reach 659.1 F g -1 .
[0067] Example 3
[0068] The difference between this embodiment and embodiment 1 is that the etching time of the Bi-BTC MOFs precursor in step (2) is 2 hours to obtain BPHM-2 nanomaterials. Other conditions are the same.
[0069] Finally, the defect-rich hollow open bismuth phosphate microsphere negative electrode material BPOHM-2 was prepared. The constant current charge and discharge (GCD) curves at different current densities are shown in the following figure: Fig. 9 As shown, it is calculated that the material is 1Ag -1 The specific capacity at a current density of 1.377 W / m2 can reach 688.6 F g / cm2. -1 .
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 1 is that BPHM-3 is treated at the same calcination temperature in an Ar atmosphere to obtain BPOHM-3Ar.
[0072] Its constant current charge and discharge (GCD) curves at different current densities are as follows: Fig.10 As shown, it is calculated that the material is 1Ag -1The specific capacity at a current density of 392.4 F g -1 .
[0073] Comparative Example 2
[0074] In order to better demonstrate the unique advantages of MOFs materials, Bi(NO 3 ) 3 ·5H 2 O sample was etched instead of Bi-BTC MOFs precursor for comparison. The steps are as follows:
[0075] Weigh 0.1 g Bi(NO 3 ) 3 ·5H 2 O powder was dispersed in 10 mL of deionized water, transferred to a round-bottom flask, and 15 mL of 0.1 mol L -1 The phytic acid solution was reacted in an oil bath at 90°C for 3 h, then centrifuged and dried. The obtained product was placed in a porcelain boat and covered the bottom of the porcelain boat. The porcelain boat was then transferred to a tube furnace and calcined at 450°C and Air for 2 h at a heating rate of 2°C min -1 After the tube furnace was cooled naturally to room temperature, sample BPNP-3 was collected.
[0076] Its constant current charge and discharge (GCD) curves at different current densities are as follows: Fig.11 shown.
[0077] The above description is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, modification, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing defect-rich hollow open bismuth phosphate microsphere negative electrode material, characterized in that: The following steps are involved: (1) dissolving bismuth nitrate pentahydrate and trimesic acid in a molar ratio of 1:(1-2) in an organic solvent, and performing a solvothermal reaction at 140-160° C. to obtain a spherical Bi-BTC MOFs precursor; Wherein, the organic solvent comprises ethanol and ethylene glycol, and the volume ratio of the ethanol to the ethylene glycol is 1:(1-3); (2) dispersing the precursor into deionized water to form a homogeneous solution, adding a phytic acid solution with a concentration of 0.05 to 0.2 mol / L, and reacting in an oil bath at 80 to 100° C. for 0.5 to 5 h to obtain a BPHM nanomaterial; (3) The prepared nanomaterial is calcined at 400-500° C. for 1-3 h to obtain defect-rich hollow open bismuth phosphate microspheres.
2. The preparation method according to claim 1, characterized in that: In the step (1), bismuth nitrate pentahydrate and trimesic acid are first dissolved in a mixed solution of ethanol and ethylene glycol in a volume ratio of 1:(1-3) in a molar ratio of 1:(1-2), ultrasonically dispersed for 20 minutes, and then subjected to a solvothermal reaction at 140-160° C. for 24 hours. The mixture is cooled to room temperature, and the precipitate is collected, washed by centrifugation, and dried at 60° C. for 12 hours to obtain a spherical Bi-BTC MOFs precursor.
3. The preparation method according to claim 1, characterized in that: In the step (1), the amount of organic solvent added is sufficient to completely dissolve bismuth nitrate pentahydrate and trimesic acid in the organic solvent.
4. The preparation method according to claim 1, characterized in that: The oil bath reaction time in step (2) is 1 to 4 hours.
5. The preparation method according to claim 1, characterized in that: In the step (2), the Bi-BTC MOFs precursor is dispersed in deionized water, and the mass volume ratio of the precursor to deionized water is 0.1 g:10 mL; after dispersion to form a homogeneous solution, 0.05-0.2 mol / L phytic acid solution is added, and the final reaction system Bi-BTC and phytic acid mass ratio is 1:1.65-66; finally, the reaction is carried out in an oil bath at 90°C for 0.5-5h, centrifuged, and dried to obtain a BPHM-X nanomaterial; wherein X represents the reaction time.
6. The preparation method according to claim 1, characterized in that: In the step (3), the prepared BPHM nanomaterial is subjected to a high-temperature calcination reaction, the high-temperature calcination temperature is 400-500° C., the heating rate is 2° C. / min; the calcination atmosphere is Air, and the reaction time is 1-3 hours, to obtain defect-rich hollow open bismuth phosphate microspheres.
7. Defect-rich hollow open bismuth phosphate microspheres prepared according to the preparation method according to any one of claims 1 to 6.
8. Application of defect-rich hollow open bismuth phosphate microspheres prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The defect-rich hollow open bismuth phosphate microspheres are used as negative electrode materials and are applied in a bismuth-based aqueous alkaline rechargeable battery system.